Analysis of fungal diversity in processed jujube products and the production of mycotoxins by typical toxigenic Aspergillus spp. - Li, Tianzhi; Ji, Hua; Sun, Jingtao; Li, Yinghao; Xu, Yue; Ma, Wenyi; Sun, Han (Frontiers in Microbiology, 2025)
Processed jujube products are susceptible to contamination by fungi such as Aspergillus spp., which produces mycotoxins that could lead to health problems in consumers. In this study, 58 samples of processed jujube products (including 5 types such as dried jujubes) were collected from different markets in Shihezi (Xinjiang, China). The fungal diversity and the fungi isolated from processed jujube products were systematically analyzed through high-throughput sequencing and molecular biological identification (based on the ITS and/or BenA and CaM regions). In total, the 105 strains of fungi were isolated and identified as belonging to the dominant genera were Aspergillus, Cladosporium, Alternaria, and Penicillium. High-throughput sequencing indicated that Alternaria, Didymella, Cladosporium, and Aspergillus were the dominant fungi in processed jujube products. ELISA showed that A. flavus produced about 19.3862–21.7583 μg/L, 6.5309–11.0411 μg/L, 0–15.4407 μg/L, 0–5.6354 μg/L, and 0–6.0545 μg/L of AFT, AFB1, AFB2, AFM1, and AFM2, respectively. In addition, concentrations of OTA produced by A. niger, A. tubingensis, and A. ochraceus were found to range from 5.2019 to 18.5207 μg/L. Therefore, the separation of Aspergillus with good mycotoxin-producing abilities from processed jujube products poses a latent threat to consumer health.